2003
DOI: 10.1177/0093854803256451
|View full text |Cite
|
Sign up to set email alerts
|

Offender Ethnicity and Mental Health Service Referrals from Juvenile Courts

Abstract: Juvenile courts play a critical role in facilitating access to mental health services for the large number of offenders with or at risk of emotional or behavioral problems. This research examines the decision of the court to refer offenders to treatment and whether offender ethnicity affects the referral decision. Results suggest that ethnicity has no independent effect on treatment recommendations. Rather, ethnicity modifies the effects of other variables, particularly legalistic variables such as petitioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
(72 reference statements)
1
23
0
Order By: Relevance
“…Some researchers have found that a referral for treatment service was one of the most common juvenile court dispositions, with 50% of supervised youth being referred for treatment (Breda, 2003). The need for treatment referrals does not seem to differ by youths' race (Martin & Grubb, 1990) in both short-term detention facilities (Rogers, Powell, & Strock, 1998) and long-term detention facilities (Glisson, 1996).…”
Section: Background Differential Treatment Theory and Youthful Offendmentioning
confidence: 99%
“…Some researchers have found that a referral for treatment service was one of the most common juvenile court dispositions, with 50% of supervised youth being referred for treatment (Breda, 2003). The need for treatment referrals does not seem to differ by youths' race (Martin & Grubb, 1990) in both short-term detention facilities (Rogers, Powell, & Strock, 1998) and long-term detention facilities (Glisson, 1996).…”
Section: Background Differential Treatment Theory and Youthful Offendmentioning
confidence: 99%
“…Client factors such as race and ethnicity have been shown to influence referral to mental health treatment. Breda (2003) found no direct effects of ethnicity on referral for treatment, but when included with other factors such as offense type and prior record, ethnicity significantly affected the likeliness of a referral. Rogers, Zima, Powell and Pumariega (2002) highlight socio-demographic factors influencing treatment referral.…”
Section: Status Of the Literaturementioning
confidence: 73%
“…There is substantial evidence that factors aside from degree of need may play a role in determining which youth receive services. For example, evidence of race and ethnicity influencing mental health service referrals is supported by the work of Breda (2003) and Rogers, Zima, Powell, and Pumariega (2002). However, these studies focused on youth in the JJS in general and are not limited to youth placed in closed custody institutions.…”
Section: Chapter Two: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations